Предмет: Математика,
автор: Аноним
(3х+у)-(-х-4у)=
(х+6у)-(8х-7у)=
(m+n)-(m-n)=
Ответы
Автор ответа:
0
(3х+у)-(-х-4у)=3х+у+х+4у=4х+5у
(х+6у)-(8х-7у)= х+6у-8х+7у=-7х+13у
(m+n)-(m-n)= m+n-m+n=2m+2n
(х+6у)-(8х-7у)= х+6у-8х+7у=-7х+13у
(m+n)-(m-n)= m+n-m+n=2m+2n
Автор ответа:
0
3a-3b-2a-2b=a-b
Автор ответа:
0
а второй пажалусьа
Автор ответа:
0
пажалуста
Автор ответа:
0
2.4c-7.2d-2.6c+1.3d=-0.2c- 5.9d
Автор ответа:
0
Спасибо
Похожие вопросы
Предмет: Биология,
автор: Lilinalin
Предмет: Русский язык,
автор: emtsoysvetlana
Предмет: Қазақ тiлi,
автор: jandarbeksagitov
Предмет: Геометрия,
автор: Аноним